A Semiotic Analysis on Confession of a Shopaholic Trailer: Roland Barthes Approach - Nur Syasya Qistina Mazeree; Norhakimin Ashaari; Nadzirah Munirah Ramli; Nur Arifah Zahiah Zuri (English Department of Faculty of Tarbiyah and Teacher Training, 2023)
Deciphering the signals in a movie trailer is undertaken to comprehend how viewers or learners receive the conveyed meanings. The objective of this study is to (1) analyze the symbols present in the